Market led development: RD strategies for agriculture in Southern Africa. Bulawayo (Zimbabwe). 30-31 Jul 2002 - Alumira, J.D.; Heinrich, G.M. (Bulawayo (Simbabwe), 2003)
Sumario (En)
Ilus.
Keywords: SORGOS; MIJOS; MERCADOS; DESARROLLO AGRICOLA; MERCADEO; APLICACION DE ABONOS; COSECHA; AFRICA